Analisis pengaruh impor barang konsumsi, impor barang modal, dan impor bahan baku/penolong terhadap PDB Indonesia Tahun 2000-2018 - Maria Nababan; Haryadi Haryadi; Rahma Nurjanah (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
The objectives of this study are (1) to determine and analyze the development of imports of consumer goods, capital goods, raw / auxiliary materials and Indonesia's GDP. (2) to determine and analyze the magnitude of the influence of imports of consumer goods, capital goods, raw / auxiliary materials on Indonesia's GDP. The method used in this research is quantitative descriptive method with multiple linear regression analysis tools with the Ordinary Least Square (OLS) method. The results of this study indicate that the development of imports of consumer goods in Indonesia in 2000-2018 has increased on average every year, the development of imports of capital goods has increased on average annually higher than imports of consumer goods, the development of imports of raw / auxiliary materials has on average experienced increase every year and followed by the development of Indonesia's GDP which increases every year. Based on the results of the analysis carried out, Import of Consumer Goods has a significant effect on Indonesia’s GDP, imports of capital goods have a significant effect on Indonesia's GDP, imports of raw / auxiliary materials have no effect on Indonesia's GDP.